Conflict of Interests in the Scientific Production on Vitamin D and COVID-19: A Scoping Review - Passini, Carolina Saggioro Meissonier; Cavalcanti, Maria Birman; Ribas, Simone Augusta; de Carvalho, Camila Maranha Paes; Bocca, Cláudia; Lamarca, Fernando (Frontiers in Public Health, 2022)
The use of scientific evidence to support the process of formulating and implementing public policies might be biased by studies funded by the pharmaceutical and food industry, which more often than not meet corporate interests. This review aimed to analyze the occurrence of conflict of interest (COI) in academic production regarding vitamin D and COVID-19, considering the facility offered during the pandemic for academic publications of heterogeneous quality. A scoping review of observational studies published in Medline, Lilacs, and Google Scholar databases was carried out. The selected studies were published between December 2019 and August 2021, focused on the relationship between vitamin D and prevention or treatment of COVID-19 in non-institutionalized individuals, with no language restrictions. Twenty-nine studies met eligibility criteria. COI was disclosed in five papers and further identified by review authors in eight other papers, meaning COI was present in thirteen papers (44.8%). Studies were funded by companies in the diagnostics, pharmaceutical and food sectors. Conclusions favorable to vitamin D supplementation were more prevalent in papers where COI was identified (9/13, 69.2%) than among papers where COI was not found (4/16, 25.0%). Omissions of disclosure of COI, funding source, and sponsor functions were observed. The identification of possible corporate political activities in scientific papers about vitamin D published during the COVID-19 pandemic signals a need for greater transparency and guideline development on the prevention of COI in scientific production.